Pharmacological Evaluation and Computational Insights into Two Pyrazole Derivatives of (E)-3-(4-chlorophenyl)-1- phenylprop-2-en-1-one - Haque, K M Ferdousul; Hossain, Md Khalid; Rashid, Mohammad A; Rahman, Mohammad Sharifur (Dhaka University Journal of Pharmaceutical Sciences, 2025)
On a global scale, cancer and oxidative stress remain major health challenges. One such class of compounds is chalcones, which are 1,3-diaryl ketones containing an α, β-unsaturated carbonyl system. These ketones serve as precursors to numerous biologically active heterocyclic frameworks, including pyrazoles. In the present study, a chlorochalcone, (E)-3-(4-chlorophenyl)-1-phenylprop-2-en-1-one (1), was prepared by condensing 4-chlorobenzaldehyde with acetophenone. It was then converted into two pyrazole derivatives, 5-(4-chlorophenyl)-3-phenyl-4,5-dihydro-1H-pyrazole (2) and 1-(5-(4-chlorophenyl)-3-phenyl-4,5-dihydropyrazol-1-yl) ethanone (3), via reaction with hydrazine hydrate followed by acetylation with acetic acid, respectively. The structures were confirmed using FT-IR and ¹H NMR spectroscopic analyses. When tested against HeLa cancer cells, all three compounds exhibited strong cytotoxic activity, reducing cell viability to below 5%. The antioxidant assays, which measured total antioxidant capacity and free radical scavenging, showed that compounds 1 through 3 had noticeable activity. Molecular docking predicted that compounds 1-3 formed strong binding interactions at the adenosine triphosphate binding site of the epidermal growth factor receptor protein (EGFR; PDB: 1M17). Compounds 1 and 2 may interact with CYP enzymes, whereas others demonstrated good oral absorption and blood-brain barrier permeability, according to Swiss ADME predictions. To the best of our knowledge, the biological and computational assays for these compounds have been conducted for the first time. Overall, the chalconepyrazole derivatives exhibited promising antioxidant and anticancer potential, warranting further biological and pharmacokinetic investigations. Dhaka Univ. J. Pharm. Sci. 24(2): 219-229, 2025 (December)